2007
DOI: 10.2193/2007-004
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Birds in Riparian and Upland Dry Forests of the Cascade Range

Abstract: We quantified breeding bird abundance, diversity, and indicator species in riparian and upland dry forests along 6 third‐ to fourth‐order streams on the east slope of the Cascade Range, Washington, USA. Upland dry forest on southerly aspects was dominated by open ponderosa pine (Pinus ponderosa) and dry Douglas‐fir (Pseudotsuga menziesii) plant associations. Upland mesic forest on northerly aspects was dominated by closed‐canopy Douglas‐fir or dry grand fir (Abies grandis) plant associations. Riparian overstor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
(50 reference statements)
1
17
0
Order By: Relevance
“…Habitat characteristics that pre-dispose riparian vegetation to supporting unique avian assemblages in southern Africa (Monadjem, 2003, this study) and elsewhere (e.g. Lehmkuhl et al, 2007), include the relative complexity of vegetation structure, particularly in arid regions (Gregory et al, 1991), and greater productivity, owing to greater soil moisture and nutrient availability (Naiman and Dé camps, 1997). Fleishman et al (2003) found that while species richness was determined by habitat structure (physiognomy), avian species composition was determined more by habitat species composition (floristics).…”
mentioning
confidence: 84%
“…Habitat characteristics that pre-dispose riparian vegetation to supporting unique avian assemblages in southern Africa (Monadjem, 2003, this study) and elsewhere (e.g. Lehmkuhl et al, 2007), include the relative complexity of vegetation structure, particularly in arid regions (Gregory et al, 1991), and greater productivity, owing to greater soil moisture and nutrient availability (Naiman and Dé camps, 1997). Fleishman et al (2003) found that while species richness was determined by habitat structure (physiognomy), avian species composition was determined more by habitat species composition (floristics).…”
mentioning
confidence: 84%
“…Many studies have revealed greater bird species diversity and abundance in riparian zones than in surrounding habitats, but this pattern is most prominent in arid regions Jakle 1985, Woinarski et al 2000). In mesic regions, the association is often weak or nonexistent (McGarigal and McComb 1992, Pearson and Manuwal 2001, Loehle et al 2005, Lehmkuhl et al 2007), especially where the transition between riparian and upland vegetation is indistinct (Wiebe andMartin 1998, Shirley 2005). Few investigators have examined the extent to which positive effects of riparian zones on bird species richness and abundance might extend into adjoining habitats.…”
Section: Resumen Efectos De La Proximidad a La Zona Riparia Sobre Lamentioning
confidence: 99%
“…, Lehmkuhl et al. ), especially where the transition between riparian and upland vegetation is indistinct (Wiebe and Martin , Shirley ). Few investigators have examined the extent to which positive effects of riparian zones on bird species richness and abundance might extend into adjoining habitats.…”
mentioning
confidence: 99%
“…Other species did not differ by treatment year, suggesting either density was not affected by thin and handpile treatments nor prescribed burning, that the affect of treatments was consistent in buffered and unbuffered streams, or that the affect of a buffer was overshadowed by an upland treatment effect. The latter may be the case because areas of mid-elevation streams can have similar vegetation composition and structure as the upland and exhibit similar species composition (Finch, 1989;Knopf and Samson, 1994;Lehmkuhl et al, 2007). Seavy and Alexander (2006) found that prescribed fire in mixed-conifer/hardwood habitats had minimal effect on shrub and canopy cover and little effect on bird abundance.…”
Section: Bird Densitymentioning
confidence: 99%